Economic assessment of major depressive disorder treatment using different therapeutic classes at ISSSTE - Ramírez, Jocelyn; Dueñas, Héctor; Galindo, Rosa-María (Jornal Brasileiro de Economia da Saúde, 2011)
Objective: The objective of the present study was to determine the cost-effectiveness associated with three therapeutic classes for treating major depressive disorder (MDD) from the public healthcare payer perspective in Mexico. Methodology: To evaluate health and cost outcomes, a previously published decision model was adapted in order to reflect the usual MDD treatment practice at the Institute for Social Security and Services for State Workers in Mexico (ISSSTE) during a 3-months time horizon. The three therapeutic classes included in the present analysis were: Selective Serotonin Reuptake Inhibitors (SSRI), Tricyclic Antidepressants (TCA) and Serotonin-Norepinephrine Reuptake Inhibitors (SNRI). Only direct medical costs were considered either generic drugs or brand-name antidepressants with patent protection were analyzed. All costs are expressed in 2010 US dollars (Exchange Rate 1 US: 12.50 MXN pesos). Results: Within the three therapeutic classes assessed, expected value for one patient with each three options was distributed as follows: 5,001; 4,215; 4,078 for SSRI, TCA, and SNRI, respectively. The alternative with a greater expected remission rate was the SNRI class. For every thousand patients treated with SNRI, TCA, and SSRI, 725, 718, and 665 patients are expected to achieve remission, respectively. For every thousand patients treated with SNRI instead of TCA, there will be 68,272 cost savings over a period of 3 months. Likewise, when compared with SSRI, savings generated by SNRI are more than 367,437 for every thousand treated patients. Conclusion: The results of the present analysis suggest that SNRI as a therapeutic class in the treatment of MDD represent a dominant strategy.